The Concept of a Smart City in the Context of Modern Research - Dziundziuk, Kateryna (Theory and Practice of Public Administration, 2022)
It was defined that a smart city is a concept of city development that involves the integration of the newest information and communication technologies in all spheres of its functioning. It was found that the components of a smart city are: smart infrastructure, smart transport, smart energy, smart health care, smart governance, smart economy, smart citizens, smart technologies. The attributes of a smart city are: sustainability, quality of life, urbanization, smartness.It was determined that the main directions of development of a smart city are society, economy, environment, governance. It was found that the main challenges of implementing the concept of a smart city are: the cost of smart city projects, the integration of ICT and physical infrastructure, the amount of data that creates a smart city, operational efficiency, the level of hydrocarbon emissions, achieving sustainability, information security, protection from natural disasters cataclysms.It was found that smart city sustainability is linked to urban infrastructure, governance, energy, climate change, pollution, waste, as well as social, economic and health issues. It was determined that the Internet of Things and big data are the most important elements of implementing the concept of a smart city. Using the Internet of Things makes smart cities possible. The main components of the Internet of Things are: an item, local network, Internet, cloud. Big data is a collection of complex data sets that are difficult to process using conventional database management tools or traditional data processing applications.It was found that the Internet of Things, big data and smart cities are closely related. The data generated by a smart city and associated with spatial and temporal tags form the basis of big data. Big data in smart cities is accumulated as a result of the work of Internet of Things sensors, websites, mobile applications, and social networks.